THE DETERMINATION OF EXPLORATION PLAY IN DEEP WATER ENVIRONMENTAL (LATE MIOCENE) OF TARAKAN BASIN (INDONESIA) WITH SEISMIC ATTRIBUTES AND ACOUSTIC IMPEDANCE INVERSION - Aminulloh, Dzikru
This studi located in Tarakan Basin. The Tarakan Basin is a basin in Indonesia where oil and natural gas have been found. Where the deep sea floor fan sandstone is one of the reservoirs that contribute to hydrocarbons, and it is the target of this research. This research purposed to know the prospect zone of hydrocarbon reservoar in the deep sea floor fan sandstone using model based accoustic impedance inversion and seismik attribute. Accoustic impedance inversion used to know the distribution of accoustic impedance’s value in deep sea floor fan sandstone. Trough amplitude and envelope attributes used to determine the energy’s distribution in the reservoir layer. This study correlated seismic attribute maps, acoustic impedance, porocity and time structure maps to determine the gas reservoir prospect zone, play system and to obtain drill point recommendations. Based on accoustic impedance map generated model based inversion the prospect reservoir zone indicated with low accoustic impedance values lower than 14500 ((ft/s)*(gr/cc)) with porocity of 26%-32% . The potential area is shown from trough amplitudo and envelope attribute with each value less than -1000 and more than 1000. Based on information from acoustic impedance, porocity, seismic attributes and related to the time structure map, the distribution area of the deep sea floor fan reservoir prospect zone is located on the eastern part of the map and continues from NE-SW along the anticline with traps in the form of structure and stratigraphy. The next recommended drill point is located along the gas reservoir prospect zone that has been determined.